Hubungan antara Pemberian Informasi dengan Pemilihan Metode atau Alat Kontrasepsi Rasional (Kajian Data Proyek SM-PFA di Jawa Tengah dan Jawa Timur Tahun 2002) - Sri Subiyatun, Djaswadi Dasuki, Budi Wahyuni (Berita Kedokteran Masyarakat (BKM), 2011)
Relationship between Information Giving and the Contraceptive Choice or Rational Contraception (Study Used SM-PFA Project Data in Central Java and East Java in 2002)Background: Family Planning programs in Indonesia have been admitted both nationally and internationally to be successful programs in decreasing birth rate. The number of contraceptive acceptors is increasing and it reflects that Family Planning programs have become the society’s need. One option of SM-PFA project conducted in 10 districts in East and Central Java aimed at increasing the Quality of Family Planning services with respect to giving information by the provider as one of important factors in the decision taking on contraceptive choice.Objective: To find out the correlation between information giving and contraceptive choice and rational contraception.Methods: It was an analytic study using cross-sectional based on the secondary data from SM-PFA project in 2002-2003 involving 1588 fertile married couples. The data analysis used was univariable with frequency distribution, bivariable with chi-square, and multivariable with logistic regression on significance level of 0.05.Results: The proportion of rational contraceptive choice in informed samples was higher than that in uniformed samples (75% and 65.3%, respectively). Factors related to this difference were maternal age less than 20 or more than 35 years, low education level, parity more than 4 children, working mothers, and women lived in urban area.Conclusion: There was significant correlation  between information giving and the contraceptive choice or rational contraception. The factors affecting the choice were maternal age, maternal education, parity, maternal occupation and the place of live.Keywords: Family Planning Program, information giving, rational contraception